NOSOCOMIAL INFECTION AND MICROBIAL BIOFILMS IN SURGERY - N. I. Gabrielyan; E. M. Gorskaya; N. I. Romanova; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
The review presents data on the role of biofilms formation by opportunistic microbes in surgery. It gives in- formation about the microbial structure of biofilms, their architecture and physiology. The attention was payed to significal importance of microbial communities, which form biofilms in surgery. Mechanisms of increased resistance of biofilms bacteria are compared with plankton. The review includes literature data on the process of formation biofilms on intravascular catheters and methods of inhibition and protection. Methods of studing formation and inhibition of biofilms in vitro and in vivo are presented. Different biotechnology methods, based on using antiadhesive, antiseptic, biophysical resources and biomaterials are discussed.